Diffuse-specular separation using binary spherical gradient illumination - Kampouris,C; Zafeiriou,S; Ghosh,A (The Eurographics Association, 2018)
We introduce a novel method for view-independent diffuse-specular separation of albedo and photometric normals withoutrequiring polarization using binary spherical gradient illumination. The key idea is that with binary gradient illumination, adielectric surface oriented towards the dark hemisphere exhibits pure diffuse reflectance while a surface oriented towards thebright hemisphere exhibits both diffuse and specular reflectance. We exploit this observation to formulate diffuse-specular separationbased on color-space analysis of a surface’s response to binary spherical gradients and their complements. The methoddoes not impose restrictions on viewpoints and requires fewer photographs for multiview acquisition than polarized sphericalgradient illumination. We further demonstrate an efficient two-shot capture using spectral multiplexing of the illumination thatenables diffuse-specular separation of albedo and heuristic separation of photometric normals.